2023
DOI: 10.1039/d3ce00296a
|View full text |Cite
|
Sign up to set email alerts
|

Stress and light sensitive dual-mechanical property of acylhydrazone crystal

Abstract: Mechanically dual-responsive molecular crystals substantially gained interest among researchers due to their significant application in various fields. Incorporation of disparate mechanical responses in the same crystalline material is still a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
(56 reference statements)
1
8
0
Order By: Relevance
“…Notably, during the observation at T m ( Z ) – 50 °C and T m ( Z ) – 60 °C under UV irradiation, when the crystal bent to a certain degree, a part of the crystal hopped away from the original position, thus exhibiting a photosalient effect (Figure S25 and Video S3). Similar photomechanical behaviors were reported for acylhydrazide derivatives by some research groups, who suggested a mechanism based on the E -to- Z isomerization. The present NC cases provide valuable contributions to these behaviors because the crystal structures of both isomers are available.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Notably, during the observation at T m ( Z ) – 50 °C and T m ( Z ) – 60 °C under UV irradiation, when the crystal bent to a certain degree, a part of the crystal hopped away from the original position, thus exhibiting a photosalient effect (Figure S25 and Video S3). Similar photomechanical behaviors were reported for acylhydrazide derivatives by some research groups, who suggested a mechanism based on the E -to- Z isomerization. The present NC cases provide valuable contributions to these behaviors because the crystal structures of both isomers are available.…”
supporting
confidence: 83%
“…For example, Aprahamian et al. achieved control of their thermal half-lives in the range of days to thousands of years and high conversion yield over 90%. , Similar high photoswitching performances have been observed for acylhydrazones. , Notably, acylhydrazones are often distinguished from hydrazones due to their molecular structures being less restricted between the E -form and Z -form. , Furthermore, acylhydrazones exhibit photoisomerization even in a solid state and thereby are promising candidates for PCLT-active crystals. However, to the best of our knowledge, there have been no reported examples of such applications of acylhydrazones.…”
mentioning
confidence: 99%
“…Crystals 1 and 2 were plastic, crystal 3 was brittle and lastly, crystal 4 was rendered elastic in nature. 28,29 In all cases, aldehydes were the same as 3,5-di- tert -butylsalicylaldehyde but the length of the linker in the molecule differs (Fig. 1a–d).…”
Section: Resultsmentioning
confidence: 95%
“…For example, Ghosh's group, Hao's group, and other teams discovered multi-stimulus responsive flexible crystals and our group demonstrated the photomechanical behavior of needle-like elastic crystals. 34–41…”
Section: Introductionmentioning
confidence: 99%